Assessing the Job Selection Criteria of Accounting Students: A Normative Approach - Umaru Zubairu; Suhaiza Ismail; Fatima Abdul Hamid (Bina Nusantara University, 2017)
This research assessed to what extent final-year Muslim accounting students in Malaysia considered Islamic principles when choosing a job after graduation. 356 final-year Muslim accounting students in four Malaysian universities were surveyed using an open-ended job selection scenario. The result shows that reality does not live up to the ideal. Only 16% of the respondents apply Islamic principles in making a job selection decision. The remaining 84% are more concerned with other criteria such as personal interests, salary considerations, and company reputation.